An explanatory study on the proxemics of personal and social spaces of the perception of selected middle class Filipino adolescents - Bellosillo, Mary Bernadette J.; Florendo, Raquel Baltazar (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The study investigated the relation of proxemics to how Middle Class Filipino adolescents perceive personal and social spaces within the home. The researcher characterized how these spaces are perceived, using the three sub-categories of proxemics which are privacy, territoriality, and distance. The characterization of these spaces further provided an understanding on how interior design plays a role in how adolescents perceive spaces. The perception of space vary from what activities are done in each space, to the preferences of each adolescent, as well as, the existing layout of each space. The researcher adopted the multi-method approach design in this study. Purposive sampling was used wherein the researcher selected (7) seven Filipino adolescents within the age range of 15-21 years old. These adolescents who belong to middle class families reside in Metro Manila. An observation sheet, survey questionnaire, and photo documentation were the primary tools used in this study. After which, the researcher tabulated, analyzed, and interpreted the gathered data using content analysis, to determine how adolescents perceive personal and social spaces using the (3) three areas of proxemics. Based from the results of the data that was analyzed, the adolescents view the bedroom as their personal space within the home. This is where they are able to focus on doing certain activities with their undivided attention. The dining area is considered to be their social space. This is where they are able to interact with their family members. Both these spaces may also be considered to be in placement of the other, depending on the needs of the adolescent at a given time. This suggests that furniture arrangement and layout play an important role in the preferences and needs of the adolescent which may be considered in designing spaces within the home.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Personal space -- Philippines; Space (Architecture)